Investigating the mechanophysical and biological characteristics of therapeutic dental cement incorporating copper doped bioglass nanoparticles. Issue 2 (February 2022) - Choe, Young-Eun; Kim, Yu-Jin; Jeon, Se-Jeong; Ahn, Jun-Yong; Park, Jeong-Hui; Dashnyam, Khandmaa; Mandakhbayar, Nandin; Knowles, Jonathan C.; Kim, Hae-Won; Jun, Soo-Kyung; Lee, Jung-Hwan; Lee, Hae-Hyoung
Highlights: Copper bioglass nanoparticles incorporated in ZPC (Cu-ZPC) was proposed. Cu-ZPC exhibited therapeutic ion releases such as Zn, Cu, Ca and Si. Cu-ZPC showed higher odontoblastic differentiation using dental pulp human cells. Cu-ZPC inhibited the growth and attachment of E. faecalis. Graphical Abstract: ga1 Abstract: Objective: This study was investigated the mechanophysical properties of zinc phosphate cement (ZPC) with or without the copper doped bioglass nanoparticles (Cu-BGn) and their biological effect on dental pulp human cells and bacteria. Materials and methods: Cu-BGn were synthesized and characterized firstly and then, the experimental (Cu-ZPC) and control (ZPC) samples were fabricated with similar sizes and/or dimensions (diameter: 4 mm and height: 6 mm) based on the International Organization of Standards (ISO). Specifically, various concentrations of Cu-BGn were tested, and Cu-BGn concentration was optimized at 2.5 wt% based on the film thickness and overall setting time. Next, we evaluated the mechanophysical properties such as compressive strength, elastic modulus, hardness, and surface roughness. Furthermore, the biological behaviors including cell viability and odontoblastic differentiation by using dental pulp human cells as well as antibacterial properties were investigated on the Cu-ZPC. All data were analyzed statistically using SPSS® Statistics 20 (IBM®, USA). p  < 0.05 (*) was considered significant, and 'NS' represents nonsignificant. Results: Cu-BGn was obtained via a sol-gel method and added onto the ZPC for fabricating a Cu-ZPC composite and for comparison, the Cu-free-ZPC was used as a control. The film thickness (≤ 25 µm) and overall setting time (2.5–8 min) were investigated and the mechanophysical properties showed no significance ('NS') between Cu-ZPC and bare ZPC. However, cell viability and odontoblastic differentiation, alkaline phosphate (ALP) activity and alizarin red S (ARS) staining were highly stimulated in the extracts from the Cu-ZPC group compared to the ZPC group. Additionally, the antibacterial test showed that the Cu-ZPC extracts were more effective than the ZPC extracts ( p  < 0.05). Significance: Cu-ZPC showed adequate mechanophysical properties (compressive strength, hardness, and surface roughness) and enhanced odontoblastic differentiation as well as antibacterial properties compared to the ZPC-only group. Based on the findings, the fabricated Cu-ZPC might have the potential for use in the field of dental medicine and clinical applications.